A Framework for Asynchronous Replication Scheme for Utility-based Computing Environment - Wan Nor Shuhadah, Wan Nik; Zhou, Bing Bing; Zomaya, Albert Y (2015)
This paper addresses a problem on implementing an asynchronous replication scheme in utility-based computing environment. The problem needs a special attention as most of the existing replication scheme in this computing system whether implicitly support synchronous replication and/or only consider read-only job. Therefore, we propose an intelligent framework that can reinforce an effective resource selection scheme by allowing the components that give impact on the performance such as resource/data freshness of the replicated system in such environment to be considered. We exploit an Update Ordering (UO) approach and reconcile these components in designing the framework. Important issues such as job propagation delay and job propagation rules are especially addressed. Our experiments show that the proposed framework is capable to become a platform of an effective resource selection scheme and achieve a good result with good system performance as compared to existing algorithms.